Effectiveness of corticosteroid therapy in patients with moderate to severe coronavirus disease 2019: a retrospective study - Sara Sadeghi; Marjan Mansourian; Sara Ebrahimi; Baran Kahid Basiri; Niloofar Nikgoftar; Soheila Jalali; Ramin Sami (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: Ne An acute respiratory infection started in Wuhan city of China in December 2019. The pathogen was discovered as a novel coronavirus from the Coronaviridae family and called the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). According to clinical symptoms and laboratory tests, coronavirus disease 2019 (COVID-19) patients are categorized as asymptomatic, mild, moderate, severe and critical state. Suggested therapies used in moderate to severe COVID-19 disease include corticosteroids, anticoagulation and antiviral drugs (e.g., remdesivir). Objectives: We reviewed the clinical outcomes associated with corticosteroid treatment for COVID-19. Patients and Methods: We planned a retrospective study with 859 patients diagnosed with SARS-CoV-2 infection who were under treatment at Khorshid hospital affiliated with Isfahan University of Medical Sciences, Isfahan, Iran (from February to May 2020). Results: A total of 859 patients were included in this study. The mean age was 63.33±15.45 years of which 43.8% (n=376) were women. We subcategorized corticosteroids by dose prescribed in smaller groups to show better results. The secondary outcome including the rate of intensive care units (ICUs) admission and death was less with corticosteroid prescription. This study showed, mortality and ICU admission were fewer in patients with ≥51 mg/d and ≥201 mg/d of methylprednisolone therapy, respectively. Conclusion: Based on this study, corticosteroid treatment can reduce both the need for ICU admission and mortality in moderate to severe COVID-19 patients. However, clinical trials are needed to investigate the effect of corticosteroid therapy on the need to mechanically ventilate a patient.